A Cambodian smallholder farmer's choice between microfinance institutes and informal commercial moneylenders: the role of risk attitude. Issue 1 (24th February 2021) - Possner, Annkathrin; Bruns, Selina; Musshoff, Oliver
Abstract : Purpose: The purpose of this paper is to examine the extent to which individual risk attitude determines a Cambodian smallholder's choice between a commercial informal loan and a credit from a licensed microfinance institution. Design/methodology/approach: The paper analyzes a sample of smallholder farmers in the Ratanakiri province in northeastern Cambodia, a country with a long history of microfinance and a saturated microcredit market. Employing a binary and a multinomial logit model, this paper assesses the effect of individual risk attitude on the choice of a financial instrument. Findings: The results reveal a statistically significant relationship between the choice of a credit source and an individual's risk attitude: On average (c.p.) the less risk averse the smallholder is, the more they tend to prefer an unlicensed commercial lender. Practical implications: The findings suggest that less risk-averse individuals tend to take up riskier and generally more expensive informal loans. Measures to increase the safe access to financial services for less risk-averse borrowers as well as improvements in financial literacy should be undertaken to protect smallholders from taking risky choices. Originality/value: Although existing studies have examined the importance of risk attitudes between credit provider and borrower, they focus mainly on the lender's perspective. This paper provides new insights on how risk attitude influences the borrower's choice in Cambodia. Thus, this study is relevant for policymakers in countries with oversaturated microcredit markets and a high prevalence of informal lenders.